Tax Amnesty Extension in Indonesia: An Analysis through the Lens of Maslahah Mursalah and Government Responsiveness - M. Dani Habibi; Mahfud Mahfud; Muhammad Sirojudin Sidiq; Anggita Vela; Moh. Taqiyuddin Saleh (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
Tax amnesty has been a significant fiscal policy tool adopted by many countries worldwide, including Indonesia. Initially introduced in 2016, the Indonesian government extended the tax amnesty program in subsequent years to enhance tax compliance and revenue collection. This paper aims to analyse the extension of tax amnesty in Indonesia through the lens of Maslahah Mursalah (public interest) and government responsiveness. Using a qualitative approach, this study examines the rationale behind the extension of tax amnesty and its implications for tax compliance and revenue generation. Additionally, it explores the concept of Maslahah Mursalah in Islamic jurisprudence and its applicability to fiscal policies such as tax amnesty. The analysis reveals that the extension of tax amnesty in Indonesia was driven by various factors, including the need to boost tax revenues, encourage voluntary disclosure of assets, and stimulate economic growth. Furthermore, the study evaluates the responsiveness of the Indonesian government to public interests and economic conditions in extending the tax amnesty program. By integrating perspectives from Islamic jurisprudence and public policy analysis, this study provides insights into the ethical and practical considerations underlying the implementation of tax amnesty. It underscores the importance of balancing public interest, fiscal objectives, and government responsiveness in designing and evaluating tax policies